2021
DOI: 10.1038/s41467-021-23900-8
|View full text |Cite
|
Sign up to set email alerts
|

Tick extracellular vesicles enable arthropod feeding and promote distinct outcomes of bacterial infection

Abstract: Extracellular vesicles are thought to facilitate pathogen transmission from arthropods to humans and other animals. Here, we reveal that pathogen spreading from arthropods to the mammalian host is multifaceted. Extracellular vesicles from Ixodes scapularis enable tick feeding and promote infection of the mildly virulent rickettsial agent Anaplasma phagocytophilum through the SNARE proteins Vamp33 and Synaptobrevin 2 and dendritic epidermal T cells. However, extracellular vesicles from the tick Dermacentor ande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 97 publications
0
45
0
1
Order By: Relevance
“…Recently, many salivary molecules were discovered to be secreted within extracellular vesicles ( Nawaz et al, 2020a ; Nawaz et al, 2020b ; Zhou et al, 2020 ; Oliva Chávez et al, 2021 ), which impact host immune responses, wound healing and feeding success of the tick ( Karim et al, 2002 ; Karim et al, 2005 ; Alarcon-Chaidez et al, 2009 ; Villarreal et al, 2013 ; Shaw et al, 2016 ; Zhou et al, 2020 ; Oliva Chávez et al, 2021 ; Pham et al, 2021 ). Interestingly, salivary extracellular vesicles can modulate the outcome of vector-borne infections, as is the case for A. phagocytophilum and Francisella tularensis ( Oliva Chávez et al, 2021 ). Extracellular vesicles also facilitate vector-borne virus infection and transmission ( Silvas et al, 2016 ; Vora et al, 2018 ; Zhou et al, 2018 ; Reyes-Ruiz et al, 2019 ; York et al, 2021 ).…”
Section: Saliva-transmission Dynamics: a Free Ride Or Hijacking The Situation?mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many salivary molecules were discovered to be secreted within extracellular vesicles ( Nawaz et al, 2020a ; Nawaz et al, 2020b ; Zhou et al, 2020 ; Oliva Chávez et al, 2021 ), which impact host immune responses, wound healing and feeding success of the tick ( Karim et al, 2002 ; Karim et al, 2005 ; Alarcon-Chaidez et al, 2009 ; Villarreal et al, 2013 ; Shaw et al, 2016 ; Zhou et al, 2020 ; Oliva Chávez et al, 2021 ; Pham et al, 2021 ). Interestingly, salivary extracellular vesicles can modulate the outcome of vector-borne infections, as is the case for A. phagocytophilum and Francisella tularensis ( Oliva Chávez et al, 2021 ). Extracellular vesicles also facilitate vector-borne virus infection and transmission ( Silvas et al, 2016 ; Vora et al, 2018 ; Zhou et al, 2018 ; Reyes-Ruiz et al, 2019 ; York et al, 2021 ).…”
Section: Saliva-transmission Dynamics: a Free Ride Or Hijacking The Situation?mentioning
confidence: 99%
“…The mite-borne rickettsia Orientia tsutsugamushi influences serum derived exosome contents during mammalian infection by altering the concentrations of specific miRNAs ( Jiang et al, 2020 ). Similarly, A. phagocytophilum changes the contents of exosomes from infected tick cells ( Oliva Chávez et al, 2021 ). To what extent other tick-borne pathogens alter salivary extracellular vesicles and how this may affect immunomodulatory potential and/or pathogen transmission is an area that remains ripe for discovery.…”
Section: Saliva-transmission Dynamics: a Free Ride Or Hijacking The Situation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hodowle komórek kleszczowych znalazły również szerokie zastosowanie w badaniach nad odpornością kleszczy na akarycydy i w doświadczeniach mających służyć opracowaniu szczepionki przeciwko kleszczom i chorobom odkleszczowym oraz poznaniu układu immunologicznego kleszczy [13,14]. Linie kleszczowe wykorzystano do badań pęcherzyków zewnątrzkomórkowych wydzielanych przez komórki kleszczy w odpowiedzi na zakażenie F. tularensis i A. phagocytophilum [15]. KLK wykorzystywane są również do oceny kompetencji gatunków kleszczy jako wektorów patogenów, czego przykładem jest zastosowanie linii z I. scapularis względem D. andersoni w odpowiedzi na zakażenie Francisella tularensis ssp.…”
Section: Bank Komórek Kleszczy I Dostępne Linie Komórkoweunclassified
“…This hypothesis was confirmed by the identification of synaptobrevin (a crucial vesicle- and exocytosis-associated protein collectively called v-SNARES) in Amblyomma americanum and the observation of low tick engorgement weights, increased tick mortality, and premature tick detachment from the host in synaptobrevin-silenced ticks underscore their vital contribution to tick feeding success ( Karim et al., 2005 ). A recent study demonstrated that EVs from Ixodes scapularis enhance tick feeding and facilitate infection of Anaplasma phagocytophilum via SNARE proteins (Vamp33 and synaptobrevin 2) and dendritic epidermal T cells, whereas, Dermacentor andersoni EVs mitigate microbial spreading of the pathogen Francisella tularensis ( Oliva Chávez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%